A polyelectrolyte membrane for saline water and a method for preparing the same
Patent Information
- Application Number
- CN202610689726.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-19
- Publication Date
- 2026-10-20
AI Technical Summary
然而,在高盐环境中,基于静电作用构筑的络合膜普遍存在稳定性不足的问题
[0025]本发明的有益效果是:与现有技术相比,本发明的有益效果在于:通过引入兼具交联与季铵化功能的化学改性步骤,在聚电解质分离层内部构建了稳定的共价交联网络,从根本上解决了传统层层自组装膜在高盐环境下因静电屏蔽而易溶胀、解离的稳定性瓶颈。本发明制备的复合纳滤膜在模拟高矿化度盐碱水及高浓度活性氯溶液中均表现出优异的长期运行稳定性。更重要的是,该改性方法通过原位生成的永久性季铵基团和交联导致的孔径收窄,协同调控了膜的电荷性质与尺寸筛分效应,不仅有效抑制了硫酸根离子因外在补偿导致的异常透过,使其截留率大幅提升,而且实现了对钙、镁等二价离子的高效截留(>94%)和对钠、氯等一价离子的选择性透过(<30%)。本发明为高矿化度盐碱水的适度脱盐资源化利用提供了一种结构稳定、选择性精准、性能可靠的新型纳滤膜材料,具有显著的工业应用前景。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention discloses a polyelectrolyte membrane for saline-alkali water and its preparation method, belonging to the field of membrane separation technology. Background Technology
[0002] The resource utilization of saline-alkali water has become an important way to alleviate water shortages and ensure the safety of agricultural and ecological water use. Based on its main ionic composition, saline-alkali water can be classified into several types, including chloride-type, sulfate-type, and carbonate-type. Among them, high-mineralization sulfate-type saline-alkali water has attracted much attention due to its greatest treatment difficulty. This type of water typically has a total dissolved solids (TDS) exceeding 1000 mg / L and is rich in Ca²⁺, Mg²⁺, SO₄²⁻, and Cl⁻ ions, exhibiting characteristics of high salinity, high hardness, and high sulfate content. Direct reuse in agricultural irrigation can easily lead to soil compaction and crop physiological drought. Traditional treatment technologies such as coagulation sedimentation and adsorption, while capable of removing suspended solids, have almost no ability to remove dissolved salts. While thermal technologies such as evaporation and crystallization can achieve complete desalination, their high energy consumption and high investment costs limit their large-scale application. Against this backdrop, membrane separation technology, due to its advantages of high efficiency and low energy consumption, has gradually become the mainstream choice for the deep treatment of saline-alkali water. Reverse osmosis (RO) technology is widely used in desalination due to its high rejection rate of dissolved salts (over 99%). However, the non-selective desalination nature of RO technology results in high energy consumption during treatment, and the extremely pure produced water poses a risk of over-treatment for many saline-alkali water reuse scenarios, such as agricultural irrigation. This not only incurs unnecessary costs but also represents a potential waste of water resources. To address these issues, the concept of "moderate desalination," proposed in recent years, offers a new approach to the resource recovery of saline-alkali water. This involves selectively removing scale-forming ions such as Ca²⁺, Mg²⁺, and SO₄²⁻, while retaining some Na⁺ and Cl⁻, based on the specific reuse scenario. This approach significantly reduces treatment energy consumption and costs while meeting water quality requirements. Nanofiltration (NF) technology, with its pore size and membrane surface charge characteristics that are between ultrafiltration and reverse osmosis, can achieve differentiated retention of ions of different valence states through the synergistic effect of size sieving and the Donnan effect. That is, it has a high retention rate for divalent ions and a low retention rate for monovalent ions, thus showing a natural advantage in moderate desalination.
[0003] Polyelectrolyte complex membranes utilize the electrostatic complexation of oppositely charged polyelectrolytes to form a dense selective layer, allowing for precise control of the separation layer's thickness, pore size, and surface charge at the nanoscale. Polyelectrolyte complexation technology provides a powerful platform for achieving ion-selective separation and offers a new approach to overcoming the limitations of traditional nanofiltration membranes in structural control. However, in high-salt environments, complex membranes constructed based on electrostatic interactions generally suffer from insufficient stability. On the one hand, high concentrations of inorganic salts can shield the electrostatic interactions between polyelectrolyte layers, leading to membrane swelling or even dissociation. On the other hand, the charge shielding effect induced by high salinity conditions weakens the electrostatic selectivity of the separation layer surface, severely limiting its application in the treatment of highly saline-alkali water. Summary of the Invention
[0004] To address the stability bottleneck of polyelectrolyte complex membranes in high-salt environments and further enhance their ion-selective separation performance, this invention proposes a novel membrane structure design strategy to develop a structurally stable, charge-tunable, and highly ion-selective polyelectrolyte complex nanofiltration membrane. Using polyanionic electrolytes and amino-containing polycationic electrolytes as building blocks, a separation layer is formed on the base membrane surface via layer-by-layer self-assembly (LBL) technology. Furthermore, a novel crosslinking agent with di-terminated haloalkanes or di-terminated epoxy groups is introduced for chemical crosslinking. This type of crosslinking agent not only reacts with the amino groups on the polycationic electrolyte, significantly enhancing the structural stability of the selective layer under harsh environments by forming a covalent bond network, but also generates quaternary ammonium groups in situ during the reaction process. The introduction of these quaternary ammonium groups creates permanent positively charged sites within the membrane, thereby regulating the surface charge properties of the membrane and the ion transport behavior within the nanoscale confinement space. This achieves efficient retention of divalent ions (Ca²⁺, Mg²⁺, SO₄²⁻) and selective permeation of monovalent ions in highly saline-alkali water.
[0005] A composite nanofiltration membrane, the composite nanofiltration membrane comprising:
[0006] A porous polymer-supported base membrane; and a separation layer disposed on the porous polymer-supported base membrane; wherein the separation layer is a polyelectrolyte multilayer membrane formed by layer-by-layer self-assembly of an amino-containing polycationic electrolyte and a polyanionic electrolyte, and the amino groups of the amino-containing polycationic electrolyte in the polyelectrolyte multilayer membrane react with a bifunctional alkylating crosslinking agent to form a covalent crosslinking network and quaternary ammonium groups.
[0007] The amino-containing polycationic electrolyte is polyallylamine hydrochloride.
[0008] The polyanionic electrolyte is sodium polystyrene sulfonate.
[0009] The difunctional alkylating crosslinking agent is a dual-terminal halocarbon crosslinking agent or a dual-terminal epoxy group crosslinking agent.
[0010] The bifunctional alkylating crosslinking agent is 2,2-bis(bromomethyl)-1,3-propanediol.
[0011] The porous polymer-supported base membrane is made of polyethersulfone, polysulfone, or polyvinylidene fluoride.
[0012] The separated layer exhibits characteristic peaks belonging to quaternary ammonium groups in the N1s spectrum of X-ray photoelectron spectroscopy (XPS) in the range of 402.0-403.5 eV.
[0013] The composite nanofiltration membrane exhibits a positive surface zeta potential within a pH range of 4.0-6.0.
[0014] A method for preparing the composite nanofiltration membrane includes the following steps:
[0015] S1: Provides a porous polymer-supported base film;
[0016] S2: On the porous polymer support substrate membrane, a polyelectrolyte multilayer membrane is formed by alternately depositing amino-containing polycationic electrolyte solution and polyanionic electrolyte solution;
[0017] S3: The base film with polyelectrolyte multilayer obtained in step S2 is reacted with a solution of bifunctional alkylating crosslinking agent to form a covalent crosslinking network and quaternary ammonium groups in the polyelectrolyte multilayer.
[0018] In step S2, the number of bilayers of the polyelectrolyte multilayer film is 2-10, preferably 3-5.
[0019] In step S2, the pH value of the amino-containing polycationic electrolyte solution is 3-9, preferably 4-6.
[0020] In step S2, the amino-containing polycationic electrolyte solution and / or the polyanionic electrolyte solution contain an inorganic salt at a concentration of 0.1-0.5 mol / L as a supporting electrolyte.
[0021] In step S3, the concentration of the bifunctional alkylation crosslinking agent solution is 0.5-4.0 g / L, preferably 1.0-3.0 g / L.
[0022] In step S3, the contact reaction time is 6-24 hours, preferably 10-15 hours.
[0023] The application of the composite nanofiltration membrane in saline-alkali water treatment is to moderately desalinate saline-alkali water, selectively retain divalent ions and allow monovalent ions to pass through.
[0024] The divalent ions include Ca. 2+ Mg 2+and / or SO4 2- The monovalent ions include Na; + K + and / or Cl - .
[0025] The beneficial effects of this invention are as follows: Compared with the prior art, the beneficial effects of this invention are that by introducing a chemical modification step with both cross-linking and quaternization functions, a stable covalent cross-linked network is constructed inside the polyelectrolyte separation layer, fundamentally solving the stability bottleneck of traditional layer-by-layer self-assembled membranes, which are prone to swelling and dissociation due to electrostatic shielding in high-salt environments. The composite nanofiltration membrane prepared by this invention exhibits excellent long-term operational stability in simulated high-mineralization saline-alkali water and high-concentration active chlorine solutions. More importantly, this modification method, through the in-situ generation of permanent quaternary ammonium groups and the pore size narrowing caused by cross-linking, synergistically regulates the charge properties and size sieving effect of the membrane. This not only effectively suppresses the abnormal permeation of sulfate ions caused by external compensation, significantly improving its retention rate, but also achieves highly efficient retention (>94%) of divalent ions such as calcium and magnesium and selective permeation (<30%) of monovalent ions such as sodium and chloride. This invention provides a novel nanofiltration membrane material with stable structure, precise selectivity, and reliable performance for the moderate desalination and resource utilization of high-mineralization saline-alkali water, and has significant industrial application prospects. Attached Figure Description
[0026] Figure 1 Effects of preparation conditions on the properties of self-assembled membranes: (a) pH of PAH solution, (b) sodium chloride concentration, (c) deposition time, (d) number of bilayers.
[0027] Figure 2 Effects of crosslinking conditions on the properties of self-assembled membranes: (a) crosslinking time, (b) crosslinking agent concentration
[0028] Figure 3 SEM images of the surface morphology of PES base film and layer-by-layer self-assembled film before and after crosslinking: (a) PES base film, (b) (PAH / PSS)3, (c) (PAH / PSS)3-CL
[0029] Figure 4 Molecular weight cutoff (a) and pore size distribution probability density function curves of PSS / PAH layer-by-layer self-assembled membranes (b)
[0030] Figure 5 XPS N1s fine spectra of PSS / PAH layer-by-layer self-assembled films: (a) (PAH / PSS)3, (b) (PAH / PSS)3-CL
[0031] Figure 6 (a) Zeta potential and (b) infrared spectra of PES base film and layer-by-layer self-assembled film before and after crosslinking
[0032] Figure 7 Single salt rejection ratio of (PAH / PSS)3 and (PAH / PSS)3-CL membranes (salt concentration: 1000 ppm, test pressure: 6 bar)
[0033] Figure 8 Retention rate of various ions in simulated mine water by (PAH / PSS)3-CL membrane (test pressure: 6 bar)
[0034] Figure 9 Separation performance of (PAH / PSS)3-CL membrane during immersion in (a) 200 ppm active chlorine solution and (b) simulated mine water for 10 days (test solution: 1000 mg / L MgSO4, operating pressure: 6.0 bar).
[0035] Figure 10 Relationship between the degree of protonation of PAH and pH Detailed Implementation
[0036] The nanofiltration membrane described in this invention has a composite structure, consisting of a porous base membrane and a separation layer constructed on its surface.
[0037] The base membrane is a polyethersulfone (PES) porous ultrafiltration membrane, designed to provide good mechanical support while ensuring the effective transport of water molecules within the membrane. This base membrane possesses a suitable pore size distribution and excellent chemical stability, providing an ideal carrier for the construction of the separation layer.
[0038] The separation layer is constructed using a layer-by-layer self-assembly technique, forming a multilayer polyelectrolyte structure composed of alternating depositions of positively charged and negatively charged polyelectrolytes. Specifically, it uses an amine-containing cationic polyelectrolyte, such as polyallylamine hydrochloride (PAH), as the polycation, and an anionic polyelectrolyte, such as sodium polystyrene sulfonate (PSS), as the polyanion, which are deposited alternately to form (PAH / PSS). n The multilayer structure, where n is an integer or half-integer from 1 to 20, has an outermost layer of separation layer capped with PSS to impart specific charge characteristics to the membrane surface.
[0039] Furthermore, the separation layer undergoes chemical crosslinking modification. A crosslinking agent containing di-terminated haloalkanes or di-terminated epoxy groups, such as (2,2-bis(bromomethyl)-1,3-propanediol, BBPD), reacts with the amino groups on the PAH segments to construct a stable covalent crosslinking network between the polyelectrolyte layers, thereby significantly enhancing the structural stability of the separation layer under high-salt conditions. During this crosslinking reaction, the amino groups of PAH undergo alkylation to generate quaternary ammonium groups in situ, thus introducing permanent positive charge sites on the membrane surface and inside the separation layer.
[0040] By controlling the number of polyelectrolyte layers and the degree of cross-linking, the pore size and surface charge density of the separation layer can be synergistically adjusted. This nanoscale separation layer combines size sieving with electrostatic separation mechanisms, providing a structural basis for the selective separation of ions of different valence states in highly salinized mine water. This method is applicable to the preparation of flat sheet membranes and hollow fiber membranes.
[0041] Example 1
[0042] The nanofiltration membrane of the present invention is prepared by the following steps:
[0043] (1) Preparation of base film
[0044] A porous ultrafiltration membrane was prepared as the base membrane using polyethersulfone (PES) as the membrane material via a phase inversion method. PES was dissolved in an organic solvent to prepare a homogeneous casting solution. After vacuum degassing, the solution was uniformly coated onto the surface of a nonwoven fabric support layer using a doctor blade with a blade gap of 200 μm. The coated membrane was then rapidly immersed in a coagulation bath, where a phase inversion occurred through the exchange of solvent and non-solvent, forming an ultrafiltration base membrane with an asymmetric porous structure. Before use, the resulting base membrane was soaked in deionized water for 24 hours to thoroughly remove residual solvent and additives and ensure complete wetting of the membrane pores.
[0045] (2) Layer-by-layer self-assembly
[0046] Polyelectrolyte solutions were prepared separately: polyallylamine hydrochloride (PAH) was dissolved in deionized water to prepare a PAH solution with a concentration of 10 g / L; sodium polystyrene sulfonate (PSS) was dissolved in deionized water to prepare a PSS solution with a concentration of 10 g / L. To control the molecular chain conformation and adsorption behavior of the polyelectrolyte during assembly, NaCl was added as a background salt to both the PAH and PSS solutions. The NaCl concentration was adjusted from 0 to 1 mol / L, and 0.4 mol / L was selected as the preferred parameter in the following examples. The pH of the PAH solution was adjusted to the range of 3 to 11 using dilute hydrochloric acid or sodium hydroxide solution; pH 5 was selected as the preferred parameter in the following examples. The pH of the PSS solution was not adjusted.
[0047] The pretreated base film is immersed in a PAH solution for 15 minutes, allowing PAH to be adsorbed onto the base film surface via electrostatic attraction. After removal, it is rinsed repeatedly with deionized water 3-5 times to remove loosely bound polyelectrolytes. The film is then immersed in a PSS solution for 15 minutes, allowing PSS to adsorb onto the PAH layer. After removal, it is rinsed again with deionized water 3-5 times. One complete PAH and PSS adsorption cycle constitutes a bilayer (referred to as layer 1), denoted as (PAH / PSS)1. Repeating this alternating deposition process yields (PAH / PSS) layers with a predetermined number of layers. nThe structure is multilayered, where n is an integer or half-integer from 1 to 5, with n=3 being the preferred parameter. The entire assembly process is carried out at room temperature, and no drying treatment is performed after each layer deposition, keeping the film surface constantly moist.
[0048] (3) Quaternization crosslinking modification
[0049] The self-assembled composite membrane was chemically crosslinked by immersing it in a crosslinking agent solution. The crosslinking agent used was 2,2-bis(bromomethyl)-1,3-propanediol (BBPD), which was dissolved in deionized water to prepare a solution with a concentration of 0–4 g / L; in the following examples, 1 g / L was selected. At room temperature, the membrane was immersed in the crosslinking agent solution, and the crosslinking reaction time was adjusted within the range of 0–24 h; in the following examples, 12 h was selected. During the reaction, BBPD underwent a nucleophilic substitution reaction with the amino groups in the PAH layer, forming a covalent crosslinked network between the polyelectrolyte multilayers, while simultaneously introducing quaternary ammonium groups. This reaction not only significantly enhanced the structural stability of the separation layer but also effectively controlled the surface charge characteristics of the membrane. After the crosslinking reaction was completed, the membrane was removed, thoroughly washed with deionized water, and then soaked in fresh deionized water for storage, with multiple water changes to completely remove residual reactants. The resulting modified nanofiltration membrane was used directly in a wet state without drying.
[0050] Comparison Experiment of Factors Affecting Parameters
[0051] The effects of four key factors—polyelectrolyte solution pH, supporting electrolyte concentration, self-assembly time, and number of assembled layers—on the separation performance of (PAH / PSS) self-assembled membranes were systematically investigated. When comparing the parameter optimization factors, one parameter was screened, while the remaining three parameters were selected using the optimal parameters mentioned above. The results are as follows: Figure 1 As shown.
[0052] The pH of the polyelectrolyte solution significantly affects the structure and performance of the membrane by regulating the degree of ionization of the weak polyelectrolyte. The testing method is as follows: The sample used was polyallylamine hydrochloride (PAH), with a molecular weight of Mw = 15000, used in powder form. Sodium hydroxide (NaOH, 1.0 mol / L standard solution) and hydrochloric acid (HCl, 10 mol / L) were used. All solutions were prepared using deionized water. The solution preparation process was as follows: To prepare a 0.2 mol / L PAH solution (based on the molar concentration of amine groups): Weigh an appropriate amount of PAH powder and dissolve it directly in pure water, adjusting the pH to approximately 3.0, corresponding to a fully protonated state. All samples were freshly prepared immediately before use and placed in sealed containers to avoid prolonged exposure to air and prevent CO2 absorption. The titration procedure is as follows: Initial volume and pH recording: Accurately transfer 2.00 mL of (PAH) sample solution into a 5 mL glass titration vessel and record the initial pH; Stepwise addition of NaOH: Use a micropipette to add 1.0 mol / L NaOH solution sequentially, with each addition being 10–40 μL. After each addition, stir with a magnetic stirrer for 10 s, then allow the system to stand for 5 min to reach equilibrium, and then read and record the pH value; Titration endpoint: Repeat the above steps until the total volume of NaOH added reaches 400 μL. This volume corresponds to the theoretical degree of neutralization. (That is, all ammonium groups are neutralized to amine groups). Each sample undergoes 8–20 liquid addition steps, the specific number of steps depending on the amount of liquid added in each step. Based on the potentiometric titration data, the degree of dissociation α (i.e., the deprotonation fraction of amine groups) is calculated according to equation (1):
[0053]
[0054] In the formula V NaOH V0 represents the cumulative volume (mL) of 1.0 mol / L NaOH added, where V0 is the initial volume of the PAH sample (2.00 mL). This formula is based on the assumption that the titration starts at a fully protonated state (α = 0). The experimentally obtained pH value is then compared with the corresponding... The values are fitted nonlinearly using the modified Henderson-Hasselbalch equation (Equation 2):
[0055]
[0056] In the formula, pKa is the apparent dissociation constant, and B is the cooperation factor (reflecting the electrostatic interaction between adjacent charged groups). The Levenberg-Marquardt algorithm was used for fitting, with a convergence condition of the sum of squared residuals being less than 10. -6 All fitting and statistical analyses were performed using Origin software. Figure 10As shown, the degree of protonation of PAH exhibits a typical S-shaped change with increasing pH, and its apparent pKa is approximately 8.9. When the pH is below 5, the amine groups on the PAH molecular chain are in a fully protonated state (α is close to 1); when the pH exceeds 10, the degree of protonation approaches 0.
[0057] like Figure 1 As shown in (a), when the pH of the PAH solution increases from 3 to 5, the water flux of the membrane remains essentially unchanged, while the MgSO4 rejection rate increases slightly from 88.4% to 90.5%. Further adjusting the pH to 11 causes a sharp drop in rejection rate to 59.4%. This trend can be attributed to the dual regulation of PAH protonation state and interlayer electrostatic interaction by pH. Under low pH conditions, the amino groups are fully protonated, and the polymer chains exhibit an extended conformation. However, the high concentration of H⁺ in the solution shields the negative charge of the PSS layer, weakening interlayer electrostatic attraction and thus inhibiting rejection performance. When the pH rises to 5, the shielding effect of H⁺ is significantly weakened, and the rejection rate increases accordingly. However, when the pH exceeds 5, PAH gradually deprotonates, the chain charge density decreases, and the resulting selective layer structure becomes loose, leading to a decrease in rejection rate and an increase in flux. In summary, pH=5 is the condition for achieving the optimal balance between permeability and selectivity.
[0058] Background salt concentration affects the adsorption behavior and membrane structure of polyelectrolytes by modulating ionic strength and electrostatic shielding effect. The effect was investigated in the NaCl concentration range of 0–1.0 mol / L, and the results are as follows: Figure 1 As shown in b, the membrane rejection rate initially increases and then decreases with increasing salt concentration, reaching its optimum at 0.4 mol / L. Under low salt conditions, the ionic strength is low, and the polyelectrolyte chains exhibit a highly extended conformation due to electrostatic repulsion, resulting in a thin and insufficiently dense adsorption layer and a low rejection rate. Moderately increasing the salt concentration enhances the counterion shielding effect, causing the molecular chains to coil into dense coils, increasing both the adsorption layer thickness and charge density, thus raising the rejection rate. However, excessively high salt concentrations lead to over-shielding, causing excessive coiling or even collapse of the molecular chains. Furthermore, the competition between high-concentration ions and the polyelectrolyte for adsorption sites on the membrane surface leads to structural damage to the adsorption layer, resulting in a gradual decrease in the rejection rate. These trends indicate that the electrostatic shielding effect has a critical transition between moderate enhancement and excessive suppression; only within the optimal salt concentration range can the conformation and adsorption state of the polyelectrolyte achieve the optimal combination.
[0059] The self-assembly time determines the degree of polyelectrolyte adsorption and structural integrity on the membrane surface. Experimental results are as follows: Figure 1As shown in Figure c, the water flux of the membrane continuously decreased with increasing assembly time, while the retention rate exhibited a characteristic of first increasing and then stabilizing, reaching its maximum value at 15 min. In the initial stage of assembly, the polyelectrolyte had not yet completely covered the membrane surface, adsorption had not reached equilibrium, the membrane surface charge intensity was insufficient, and the retention performance was poor. As time progressed, the polyelectrolyte gradually adsorbed and reached dynamic equilibrium, the monolayer thickness tended to stabilize, and the charge density also reached saturation, at which point the membrane's retention performance was optimal. Further extending the assembly time had limited effect on improving the retention performance. Based on a comprehensive consideration of membrane fabrication efficiency and separation performance, 15 min was chosen as the assembly time for subsequent experiments.
[0060] The number of assembled layers directly determines the thickness and surface charge characteristics of the separation layer, and is a crucial structural parameter for controlling membrane performance. For example... Figure 1 As shown in Figure d, as the number of bilayers increases from 1 to 5, the water permeability of the membrane continuously decreases, while the MgSO4 rejection rate tends to stabilize (approximately 91.8%) after the number of bilayers reaches 3. In the early stages of deposition, the polyelectrolyte does not adequately cover the base membrane surface, resulting in structural defects and a low rejection rate. As the number of layers increases, the selective layer gradually densifies, significantly improving the rejection rate, but the extended water molecule transport path leads to a decrease in permeability. When the number of layers reaches 3, the surface charge density and adsorption capacity of the membrane tend to reach a steady state, and the rejection performance is basically stable. Further increasing the number of layers has limited effect on improving the rejection rate, but at the cost of sacrificing permeability. Therefore, a bilayer number of 3 is a better choice that balances rejection performance and permeation flux.
[0061] Effect of crosslinking conditions on membrane properties
[0062] The effects of two key process parameters, crosslinking time and crosslinking agent concentration, on the separation performance of (PAH / PSS) 3-CL membranes were investigated. The results are summarized in […]. Figure 2 .
[0063] Crosslinking time is a crucial parameter for regulating the structural transformation of polyelectrolyte multilayer membranes. With a fixed BBPD concentration of 2 g / L, the pure water flux and MgSO4 rejection rate of the membrane were investigated at different crosslinking times (0, 6, 12, and 24 h). The results are as follows: Figure 2As shown in Figure a, the water flux of the membrane continuously decreased as the cross-linking reaction proceeded: the flux of the uncross-linked membrane was 9.59 L·m⁻²·h⁻¹·bar⁻¹, decreasing to 7.45 L·m⁻²·h⁻¹·bar⁻¹ after 6 h of cross-linking, and further decreasing to 6.29 L·m⁻²·h⁻¹·bar⁻¹ after 12 h. After this, the flux remained relatively stable within the range of 6.38–6.63 L·m⁻²·h⁻¹·bar⁻¹ for up to 24 h. Simultaneously, the retention rate exhibited a pattern of initial rapid increase followed by stabilization: the retention rate of MgSO₄ by the original membrane was 91.4%, significantly increasing to 96.6% after 6 h of cross-linking, further increasing to 98.39% after 12 h, and remaining around 98.6% after 24 h, with a significantly slower increase. These phenomena can be explained by the cross-linking reaction mechanism. In the initial stage of the reaction, BBPD molecules rapidly undergo nucleophilic substitution reactions with the amino groups on the PAH chain segments, gradually building a covalent cross-linked network in the original electrostatically-dominated interlayer. The separation layer transforms from a relatively loosely packed structure into a more dense three-dimensional network, reducing the membrane pore size, increasing the resistance to water molecule transmembrane flow, decreasing flux while enhancing size sieving, and significantly increasing the rejection rate. After 12 hours of reaction, the active amino sites available for reaction are essentially exhausted, the cross-linking density tends to saturate, and the membrane structure enters a relatively stable state, where neither flux nor rejection rate changes significantly.
[0064] The effect of crosslinking agent concentration on membrane performance exhibits different regulatory characteristics. With a fixed crosslinking time of 12 h, the effect of BBPD concentration in the range of 0–4 g / L was investigated, and the results are as follows: Figure 2As shown in b, with increasing crosslinking agent concentration, membrane flux initially decreased and then slightly increased, while the rejection rate experienced a rapid increase before stabilizing. Specifically, the flux of the uncrosslinked membrane was 9.67 L·m⁻²·h⁻¹·bar⁻¹, which decreased to 7.35 L·m⁻²·h⁻¹·bar⁻¹ at a BBPD concentration of 1 g / L, further decreased to 6.25 L·m⁻²·h⁻¹·bar⁻¹ at 2 g / L, and then slowed down to 6.12 L·m⁻²·h⁻¹·bar⁻¹ and 6.38 L·m⁻²·h⁻¹·bar⁻¹ after further increasing to 3-4 g / L. Regarding retention rate, the initial membrane was 91.25%, which increased to 95.25% after crosslinking at 1 g / L, significantly rising to 98.12% at 2 g / L, and reaching 98.25% and 97.86% at 3 g / L and 4 g / L, respectively, basically maintaining around 98%. Analysis suggests that at low concentrations, the number of BBPD molecules in the system is limited, only forming crosslinking points between some polyelectrolyte chains, resulting in an imperfect network structure and insufficient membrane pore size shrinkage. When the concentration increases to 2 g / L, the amino active sites and crosslinking agent molecules come into full contact, forming a relatively dense covalent network, significantly increasing the retention rate and reducing the flux to a lower level. Further increasing the concentration to 3-4 g / L, due to the limited number of amino groups that can participate in the reaction, the crosslinking density tends to saturate, the membrane structure is basically stable, and the retention rate no longer increases significantly.
[0065] comprehensive Figure 2 a and Figure 2 The results from b show that when the crosslinking time is 12 h and the BBPD concentration is 2 g / L, the membrane maintains a high water flux while achieving a MgSO4 rejection rate of over 98%. Further increasing the crosslinking time or concentration has limited effect on performance improvement. Therefore, this condition was determined to be the optimal crosslinking process for preparing (PAH / PSS)3-CL membranes.
[0066] Based on the optimal preparation parameters determined in the above steps, the following tests and characterization were performed:
[0067] The surface of the PES-based membrane has an open and uniform microporous structure, exhibiting typical characteristics of a porous ultrafiltration membrane. This provides channels for water molecule transport and also provides sufficient sites for polyelectrolyte deposition. Figure 3 (a). After layer-by-layer self-assembly, the surface of the (PAH / PSS)3 membrane transforms from a porous state to a smooth and dense state, completely covering the original micropores, and no obvious defects are observed. Figure 3 (b) indicates that a structurally complete separation layer was formed. After further BBPD crosslinking, the membrane surface remained smooth and dense, and the continuity and integrity of the separation layer were not compromised. Figure 3 (c). This indicates that the crosslinking reaction mainly occurs inside the polyelectrolyte layer, enhancing the stability of the membrane structure without sacrificing the morphological integrity of the separation layer.
[0068] The test results for molecular weight cutoff and pore size distribution are as follows: Figure 4 As shown in Figure a, the molecular weight cutoff of the (PAH / PSS)3 membrane before crosslinking was 282 Da, which decreased to 246 Da after crosslinking. This indicates that covalent crosslinking tightens the separation layer structure, pushing the separation window towards a smaller molecular scale. Changes in pore size distribution further corroborate this trend. Figure 4 As shown in Figure b, the pore size distribution of the membrane before crosslinking ranges from 0.12 to 0.69 nm, with a peak at 0.31 nm. After crosslinking, the distribution range narrows to 0.15 to 0.60 nm, and the peak shifts slightly forward to 0.30 nm. BBPD crosslinking does not uniformly shrink all pore sizes, but rather tends to trim the large and small pores at both ends of the distribution, making the membrane pore structure more homogeneous. The reduced molecular weight cutoff and narrowed pore size distribution after crosslinking indicate a further enhanced size sieving effect, providing a more ideal structural basis for achieving moderate desalination in high-salinity mine water treatment.
[0069] The detailed spectrum of XPSN1s is as follows: Figure 5 As shown, the N1s spectrum of the pre-crosslinked membrane exhibits a broadened envelope peak in the range of 398–402 eV, mainly attributed to the primary amines (-NH2) on the PAH chain and their protonated forms (-NH3⁺), indicating that nitrogen exists in the separation layer in the form of CN / NH. Figure 5 (a) After BBPD crosslinking, a new peak appeared at 402.7 eV in the N1s spectrum, which coincided with the characteristic peak position of nitrogen atoms in the quaternary ammonium salt (R4N⁺). At the same time, the intensity of the original CN / NH peak decreased, indicating that the crosslinking reaction generated quaternary ammonium groups and consumed some of the primary amine groups. Figure 5 (b).
[0070] Zeta potential and FTIR spectrum as follows Figure 6 As shown, Figure 6 As shown in Figure a, the zeta potentials of the three membranes exhibit significant differences with pH. The PES-based membrane is negatively charged across the entire pH range, stemming from the stable dissociation of sulfonic acid groups in the molecular chain, providing a good substrate for polyelectrolyte adsorption. The (PAH / PSS)3 membrane, capped with PSS, has an isoelectric point of pH 4.9: under acidic conditions, the protonated amino groups in the PAH layer contribute positive charges, resulting in a positively charged membrane surface; under alkaline conditions, sulfonic acid groups dominate, leading to a negatively charged membrane surface. After BBPD crosslinking, the membrane isoelectric point rises to pH 6.2, and the negative charge weakens, attributed to the partial neutralization of the negative charge contribution from the sulfonic acid groups by the quaternary ammonium groups (R4N⁺) generated in situ during the crosslinking reaction. Figure 6Figure b shows the infrared spectra of the PES-based membrane, the (PAH / PSS)3 membrane, and the (PAH / PSS)3-CL membrane. Compared with the PES-based membrane, the (PAH / PSS)3 membrane exhibits new absorption peaks at 3500–3400 cm⁻¹ and 1650–1590 cm⁻¹, which are attributed to the NH stretching and bending vibrations of the amino groups in PAH, respectively, indicating that the polyelectrolyte was successfully deposited on the surface of the base membrane. Compared with before crosslinking, the characteristic peak intensities of the (PAH / PSS)3-CL membrane at the above two locations are significantly weakened. This is attributed to the crosslinking reaction between BBPD and the amino groups, where some primary amino groups are consumed and converted into quaternary ammonium groups.
[0071] Figure 7 The retention performance of (PAH / PSS)3 membranes for various single salts before and after crosslinking was compared. For the (PAH / PSS)3 membrane, the retention rate of Na2SO4 was significantly lower (25.34%), even lower than that of NaCl (61.38%). This anomaly cannot be explained by traditional pore size sieving or the Donnan effect. According to literature reports, this is due to the excessive compensation of PAH in the uncrosslinked membrane, which contains a large number of amino groups that are not paired with PSS. These amino sites interact with SO4²⁻ through external compensation, significantly enhancing the adsorption and diffusion capacity of SO4²⁻, thus leading to an abnormally low retention rate.
[0072] After BBPD crosslinking, the membrane's rejection rate for Na2SO4 significantly increased to 70.13%, while the rejection rate for monovalent chloride salts such as NaCl and KCl slightly decreased. This change is attributed to the comprehensive regulatory effect of the crosslinking reaction: the crosslinking agent reacts with amino groups to generate quaternary ammonium groups, consuming amino sites that can participate in external compensation and inhibiting the adsorption and diffusion of SO4²⁻. For monovalent chloride salts, the slight decrease in rejection rate after crosslinking is related to the weakened electrostatic repulsion of Cl⁻ after the membrane surface becomes more positively charged. This selective regulation meets the treatment requirements for moderate desalination of mine water, namely, maintaining preferential permeability of monovalent ions while efficiently retaining divalent SO4²⁻.
[0073] Simulated mine water separation performance test:
[0074] Table 1. Simulated Mine Water Composition Table
[0075] Parameters Unit Artificial mine water <![CDATA[Na + ]]> mg / L 973.53 <![CDATA[Ca 2+ ]]> mg / L 486.38 <![CDATA[Mg 2+ ]]> mg / L 164.36 <![CDATA[SO4 2- ]]> mg / L 2135.24 <![CDATA[Cl - ]]> mg / L 1104.53 <![CDATA[HCO3 - ]]> mg / L 324.45 EC mS / cm 8.25 TDS g / L 5.13 pH / 7.44
[0076] Figure 8The retention performance of the (PAH / PSS)3-CL membrane for multi-component ions in simulated mine water was demonstrated. The results showed that the membrane exhibited excellent retention capacity for divalent ions, with retention rates of 95.56%, 96.62%, and 94.27% for Ca²⁺, Mg²⁺, and SO₄²⁻, respectively; while the retention rates for monovalent ions were significantly lower, with retention rates of 28.35%, 16.36%, and 19.48% for Na⁺, Cl⁻, and HCO₃⁻, respectively.
[0077] This selective separation characteristic can be explained from the perspective of an external compensation mechanism. For (PAH / PSS)3-CL membranes, the cross-linking reaction consumes most of the amino groups. According to literature reports, SO4²⁻ has a high affinity for amino groups, and in uncross-linked membranes, an external compensation effect preferentially occurs, resulting in an abnormally low rejection rate. After cross-linking, due to the significant reduction in the number of amino groups, the external compensation effect of SO4²⁻ is significantly suppressed, and its transmembrane transport is mainly controlled by the size sieving effect. In addition, the narrowing of the membrane pore size after cross-linking contributes to the high rejection rate of SO4²⁻. For divalent cations Ca²⁺ and Mg²⁺, their high rejection rates are mainly attributed to the size sieving effect. For monovalent ions, the smaller hydration radius and the surface charge properties of the membrane together lead to their lower rejection rates.
[0078] This ion separation characteristic meets the treatment requirements for moderate desalination of highly salinized mine water, that is, while efficiently retaining divalent ions, it maintains the preferential permeability of monovalent ions.
[0079] Figure 9 The operational stability of the (PAH / PSS) 3-CL membrane was investigated in two typical environments. Figure 9 As shown in Figure a, during continuous immersion in 200 ppm active chlorine solution for 10 days, the membrane's MgSO4 rejection rate remained consistently between 97% and 98%, and the water flux fluctuation was less than 5%, indicating that the cross-linked structure endows the membrane with good antioxidant properties. After immersion in a simulated mine water environment for 10 days, the membrane's rejection rate and flux also remained stable, without significant decline. Figure 9 (b). The above results confirm that the (PAH / PSS)3-CL membrane exhibits excellent operational stability under oxidizing media and actual mine water conditions, providing strong support for its long-term application in complex water treatment scenarios.
Claims
1. A composite nanofiltration membrane, characterized in that, The composite nanofiltration membrane comprises: A porous polymer-supported base membrane; and a separation layer disposed on the porous polymer-supported base membrane; wherein the separation layer is a polyelectrolyte multilayer membrane formed by layer-by-layer self-assembly of an amino-containing polycationic electrolyte and a polyanionic electrolyte, and the amino groups of the amino-containing polycationic electrolyte in the polyelectrolyte multilayer membrane react with a bifunctional alkylating crosslinking agent to form a covalent crosslinking network and quaternary ammonium groups.
2. The composite nanofiltration membrane according to claim 1, characterized in that, The amino-containing polycationic electrolyte is polyallylamine hydrochloride; the polyanionic electrolyte is sodium polystyrene sulfonate.
3. The composite nanofiltration membrane according to claim 1, characterized in that, The difunctional alkylating crosslinking agent is a dual-terminal halocarbon crosslinking agent or a dual-terminal epoxy group crosslinking agent.
4. The composite nanofiltration membrane according to claim 1, characterized in that, The porous polymer-supported base membrane is made of polyethersulfone, polysulfone, or polyvinylidene fluoride; the composite nanofiltration membrane has a positive surface zeta potential in the pH range of 4.0-6.
0.
5. A method for preparing a composite nanofiltration membrane as described in any one of claims 1-4, characterized in that, Includes the following steps: S1: Provides a porous polymer-supported base film; S2: On the porous polymer support substrate membrane, a polyelectrolyte multilayer membrane is formed by alternately depositing amino-containing polycationic electrolyte solution and polyanionic electrolyte solution; S3: The base film with polyelectrolyte multilayer obtained in step S2 is reacted with a solution of bifunctional alkylating crosslinking agent to form a covalent crosslinking network and quaternary ammonium groups in the polyelectrolyte multilayer.
6. The method according to claim 5, characterized in that, In step S2, the number of bilayers in the polyelectrolyte multilayer film is 2-10, preferably 3-5; the pH value of the amino-containing polycationic electrolyte solution is 3-9, preferably 4-6; and the deposition time for each deposition of the amino-containing polycationic electrolyte solution and the polyanionic electrolyte solution is 5-20 min.
7. The method according to claim 5, characterized in that, In step S2, the amino-containing polycationic electrolyte solution and / or the polyanionic electrolyte solution contains an inorganic salt at a concentration of 0.1-1 mol / L as a supporting electrolyte; the pH range of the amino-containing polycationic electrolyte solution is 3-11.
8. The method according to claim 5, characterized in that, In step S3, the concentration of the bifunctional alkylation crosslinking agent solution is 0.5-4.0 g / L, preferably 1.0-3.0 g / L; the contact reaction time is 6-24 hours, preferably 10-15 hours.
9. The application of the composite nanofiltration membrane as described in any one of claims 1-8 in saline-alkali water treatment, characterized in that, The application is to moderately desalinate saline water, selectively retaining divalent ions and allowing monovalent ions to pass through. The application according to claim 9 is characterized in that, The divalent ions include Ca. 2+ Mg 2+ and / or SO4 2- The monovalent ions include Na; + K + and / or Cl - .